C♯ developer's guide to ASP.NET, XML, and ADO.NET - McManus, Jeffrey P. (Addison-Wesley, 2002)
This is the book every C# developer needs to read to understand how to create effective Internet applications using ASP.NET. As recognized experts in the field, Jeffrey P. McManus and Chris Kinsman explain how to build applications through effective use of ASP.NET, XML, and ADO.NET. In addition, this book will provide: Information about the Common Language Runtime and .NET Foundation Classes, which form the building blocks for application development in the .NET universe Practical C# code examples that illustrate operations used most often by application developers Thorough reference material to the objects available in the Foundation Class libraries 0672321556B11152002.